Towards Genotype-Specific Care for Chronic Hepatitis B: The First 6 Years Follow Up From the CHARM Cohort Study. (3rd November 2019) - Davies, Jane; Smith, Emma L; Littlejohn, Margaret; Edwards, Rosalind; Sozzi, Vitina; Jackson, Kathy; Mcguire, Katie; Binks, Paula; Cowie, Benjamin C; Locarnini, Stephen; Davis, Joshua S; Tong, Steven Y C
Abstract: Objective: There is increasing evidence to suggest that, among those with chronic hepatitis B virus infection, the natural history and rate of progression to cirrhosis and hepatocellular carcinoma is influenced by hepatitis B virus genotype. The unique hepatitis B virus genotype C4 circulates among Indigenous Australians. The aim of this work is to describe the process of establishing this cohort and review the first 6 years of available data in an effort to understand the real-world clinical care and natural history of this subgenotype. Method: We followed a longitudinal cohort of Indigenous Australians from the Northern Territory of Australia with established subgenotype C4 infections. We assigned phases of disease according to Gastroenterological Society of Australia and Asian Pacific Association for the Study of the Liver criteria using clinical and laboratory information that had been collected for clinical management. Results: Of 193 patients followed over a median of 38 months, 58 (30%) individuals transitioned from 1 disease phase to another, 10 (5%) cleared hepatitis B e antigen, and 6 cleared hepatitis B surface antigen (3%). In this relatively young cohort (median age 40.3 years), 26 (13%) had cirrhosis by the end of the follow up period, with the majority of these being in the immune control phase of disease. Conclusions: In this cohort of hepatitis B subgenotype C4 patients, we report an aggressive and dynamic clinical phenotype. High rates of cirrhosis at a young age appear to occur in the early phases of disease. Abstract : Hepatitis B subgenotype C4 has been found exclusively in Indigenous Australians. This subgenotype appears to be associated with older age of e antigen seroconversion and relatively high rates of cirrhosis.